Análise econômica da eficiência da produção de cana-de-açúcar de fornecedores do Estado do Paraná - Melo, Cármem Ozana de [UNESP]; Esperancini, Maura Seiko Tsutsui [UNESP] (EIA Energy in Agriculture, 2012)
The sugarcane industry has been important in the Brazilian economy since the colonial period. The search for alternative energy sources has gained more prominence, by offering a product generating clean energy. With the opening of the Brazilian economy, the sector has undergone transformations operating in a free market environment requiring greater efficiency and competitiveness of those involved in order to stay in business. This scenario is producer/supplier independent, and social aspects related to their stay in the market. Although its share in sugarcane production is smaller than the plant itself, it is still considerable having reached around 20% to 25% in 2008 by employing labor, also production factors had an important economic impact in the regions where they operate. Therefore, this study aimed to estimate the economic efficiency and production of independent sugarcane producers in the state of Paraná through the DEA model. The Data envelopment analysis (DEA) is a nonparametric technique that, using linear programming constructs production borders from production units that employ similar technological processes to transform inputs into outputs.The results showed that of the total surveyed, 13.56% had maximum efficiency (an efficiency score equal to 1). The average efficiency under variable returns to scale (BCC-DEA) was 0.71024. One can thus conclude that for the majority of the samples collected, it might be better use of available resources to the in order to obtain the economic efficiency of the production process.

A atividade canavieira tem importância na economia brasileira desde o período colonial. Com a busca de fontes alternativas de energia ganhou maior destaque, por ofertar um produto gerador de energia limpa. Com a abertura da economia brasileira, o setor passou por transformações, atuando em ambiente de livre mercado, o que exigiu dos agentes envolvidos maior competitividade e eficiência a fim de permanecer na atividade. Nesse cenário encontra-se o produtor/fornecedor independente que, além dos aspectos sociais ligados à sua permanência no mercado, sua participação na produção de cana, apesar de menor que a da própria usina, não deixa de ser considerável, situando em torno de 20% a 25% em 2008, empregando mão de obra e outros fatores de produção, com repercussões econômicas importantes nas regiões onde atuam. Neste sentido, este trabalho teve como objetivo estimar a eficiência econômica da produção de cana-de-açúcar dos produtores independentes do estado do Paraná, através do modelo DEA. A Análise Envoltória de Dados (DEA) é uma técnica não paramétrica que, por meio de programação linear, constrói fronteiras de produção de unidades produtivas que empregam processos tecnológicos semelhantes para transformar insumos em produtos. Os resultados obtidos permitiram concluir que, do total dos pesquisados, 13,56% apresentaram eficiência máxima (escore de eficiência igual a 1). A eficiência média, sob retornos variáveis à escala (DEA-BCC), foi de 0,71024. Pode-se então concluir que, para a maioria da amostra pesquisada, poderia haver melhor uso dos recursos que dispõem, a fim de se obter a eficiência econômica no processo produtivo.
Economic efficency analysis of sugarcane producton suppliers in the State of Paraná
Keywords: Economic efficiency; Bioenergy; Production process; Eficiência econômica; Agroenergia; Processo produtivo